Red Wine Polyphenolics Increase LDL Receptor Expression and Activity and Supress the Secretion of ApoB100 from Human HepG2 Cells - Pal, Sebely; Ho, Nerissa; Santos, C.; Dubois, Paul; Mamo, John; Croft, K.; Allister, Emma (American Society for Nutrition, 2003)
Epidemiologic studies suggest that the consumption of red wine may lower the risk of cardiovascular disease. The cardioprotective effect of red wine has been attributed to the polyphenols present in red wine, particularly resveratrol (a stilbene, with estrogen-like activity), and the flavonoids, catechin, epicatechin, quercetin and phenolic acids such as gallic acid. At present, very little is known about the mechanisms by which red wine phenolic compounds benefit the cardiovascular system. Therefore, the aim of this study was to elucidate whether red wine polyphenolics reduce lipoprotein production and clearance by the liver. Cultured HepG2 cells were incubated in the presence of dealcoholized red wine, alcohol-containing red wine and atorvastatin for 24 h. The apolipoprotien B100 (apoB100) protein (marker of hepatic lipoproteins) was quantified on Western blots with an anti-apoB100 antibody and the enhanced chemiluminescence detection system. Apolipoprotein B100 levels in the cells and that secreted into the media were significantly reduced by 50% in liver cells incubated with alcohol-stripped red wine compared with control cells. This effect of dealcoholized red wine on apoB100 production in HepG2 cells was similar to the effect of atorvastatin. Apo B100 production was significantly attenuated by 30% in cells incubated with alcoholized red wine, suggesting that the alcohol was masking the effect of red wine polyphenolics. Apo B100 production was significantly attenuated by 45% with the polyphenolic compounds resveratrol and quercertin. In addition, dealcoholized and alcoholized red wine and atorvastatin significantly increased 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase mRNA and LDL receptor binding activity relative to controls. Dealcoholized red wine also increased LDL receptor gene expression. Collectively, this study suggests that red wine polyphenolics regulate major pathways involved in lipoprotein metabolism.